An innovative digitization evaluation scheme for Spatio-temporal coordination relationship between multiple knowledge driven rural economic development and agricultural ecological environment: Coupling coordination model analysis based on Guangxi - Wei Liu; Wei Zhou; Lexian Lu (Journal of Innovation & Knowledge (JIK), 2022)
The agricultural ecological environment is the premise and foundation of rural economic development and the rural economy is an important manifestation of the vitality of the agricultural ecological environment. Taking 14 prefecture-level cities in Guangxi as the research object, this paper collects and sorts out the relevant data indicators of rural economy and agricultural ecological environment of them from 2007 to 2019, constructs the evaluation index system, calculates the development index by using the comprehensive index function, and finally uses an innovative digitization evaluation scheme to further evaluate the spatiotemporal coupling and coordination relationship between the rural economy and agricultural ecological environment. The following conclusions are ultimately drawn. First, the comprehensive level index of the rural economy shows linear growth with unbalanced regional development (values from 0.306 to 0.598). Second, the comprehensive index of the agricultural ecological environment shows fluctuating growth with obvious regional differences (values from 0.264 to 0.483). Third, the development of rural economy and agricultural ecological environment is not synchronized, and there is mutual influence. Fourth, the coordination level of the rural economy and agricultural ecological environment is low (coupling values from 0.369 to 0.513). Then, policy inspirations are proposed. First, the investment in agricultural science and technology innovation should be increased and the modern agricultural technology system. Second, agricultural industrial structure should be optimized and the agricultural industrial chain. Third, the construction of agricultural infrastructure should be improved, and the high-quality development of agriculture should be promoted. Fourth, the education of ecological civilization should be strengthened, and awareness of ecological and environmental protection should be established. Fifth, they should strengthen education and training and cultivate new professional farmers. Sixth, they should improve the utilization rate of land and enhance the arable land production capacity.
Keywords: 650; Agricultural ecological environment; An innovative digitization evaluation scheme; Rural economic development